SINTESIS SALISILANILIDA DARI KOMPONEN UTAMA MINYAK GANDAPURA - Sulistyo, Rinda; Suratmo, Suratmo; Retnowati, Rurini (Jurnal Ilmu Kimia Universitas Brawijaya, 2015)
The synthesis of salicylanilide from the main components of gandapura oil was conducted in this research through substitution reaction. This research was carried out by reacting methyl salicylate in gandapura oil with aniline by refluxing for 8 hour. The products were identified using IR spectrophotometer and gas chromatography mass spectrometry (GC-MS). Result of identification with IR spectrophotometer showed peaks at 3380.98 cm-1 which is a secondary amide N-H group and peak at 1677.95 cm-1 which is the absorption of amide carbonyl C=O group. The results of the GC-MS identification obtained 4 peaks. Peak with a retention time of 11.505 minutes is showed the presence of methylsalicylate compounds, whereas the peak with aretention time of 22.890 minutes and with 0.26% area has a value for m/z 213 is suspected to be the synthesized compounds (salicylanilide).